2005
DOI: 10.1016/s0210-4806(05)73208-3
|View full text |Cite
|
Sign up to set email alerts
|

Uréter circumcavo no obstructivo

Abstract: We report a case on circumcavum ureter without obstruction or type two, according the Batenson and Atkinson's classification, in a forty-nine year old man. It was diagnosticated for a gross haematuria and renoureteral pain, because of a simultaneous urinary tract infection. We emphasize its absence of the typical morphology and obstruction signs. After twelve months the patient is still asymptomatic, without any medical or surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…There is little discussion on the role of watchful waiting but it has been suggested for asymptomatic patients with minimal calicectasis [4] . Cao Avellaneda et al reported a case of type two retrocaval ureter managed conservatively [5] . However, there is no precedent literature reporting conservative management of type one retrocaval ureters.…”
Section: Discussionmentioning
confidence: 99%
“…There is little discussion on the role of watchful waiting but it has been suggested for asymptomatic patients with minimal calicectasis [4] . Cao Avellaneda et al reported a case of type two retrocaval ureter managed conservatively [5] . However, there is no precedent literature reporting conservative management of type one retrocaval ureters.…”
Section: Discussionmentioning
confidence: 99%
“…Various types of the anomalies have been identified with the help of cross-sectional imaging (3). Imaging results also serve as a valuable tool for clinicians to re-evaluate several clinical conditions, including haematuria (4) and urinary tract infection (5) of unknown aetiology, as well as recurrent deep vein thrombosis (DVT) and pulmonary embolism (6,7), which used to be refractory to conventional treatment and is currently considered to be related to the underlying anomalies of the IVC.…”
Section: Introductionmentioning
confidence: 99%